A Legal Study of the Dynamics of the Determination of the Age Limit of Candidates for President and Vice President by the Constitutional Court in Indonesia - Loso Judijanto; Andri Triyantoro; Fauzan Fauzan (Westscience Press, 2024)
The determination of age limits for presidential and vice-presidential candidates in Indonesia has been the subject of debate in legal and public circles. This research uses comprehensive analysis to explore the legal dynamics surrounding the age eligibility criteria for this high executive office, focusing on judicial interpretations, public perspectives, and policy implications. By examining constitutional provisions, judicial interpretations, public discourse and scholarly works, this research sheds light on the complexities and implications of age-limit provisions in Indonesia's electoral system. The findings contribute to a deeper understanding of the legal, political and social dimensions that shape age eligibility criteria and their implications for democratic governance.